Analysis of Factors Affecting Indonesian Tuna Exports to The United States in 2010-2021 - Efendi, Marshela Putri; Marseto, Marseto (Lembaga Riset dan Inovasi Al-Matani, 2022)
Tuna is an essential commodity in the fishing and marine industries due to its high economic value and ability to generate foreign exchange for the country. This study aims to see the correlation between the amount of tuna produced in Indonesia, the exchange rate, and the export price of tuna with the volume of Indonesian tuna exports to the United States. This study uses time series data from 2010 to 2021 and uses multiple linear regression (Ordinary Least Square) method for data analysis. The findings of this study reveal that Indonesia's tuna production quantity, exchange rate, and tuna export price jointly affect the amount of Indonesia's tuna exports to the United States. However, the volume of Indonesian tuna production does not have a significant or detrimental impact on the volume of Indonesian tuna exports to the United States. In contrast, the exchange rate and tuna export prices have a negative and significant impact on the volume of Indonesian tuna exports to the United States.